Penerapan Model Pembelajaran PJBL untuk Meningkatkan Hasil Belajar Peserta Didik Kelas X MPK 3 SMK Adhikawacana Surabaya - Yohana Sueng, Maria; Diana Sinta, Ade; Anis Eka Setiyorini, Diah; Widyawati, Dwi; Aji Suspito, Maulana; Puspasari, Durinta; Istinaroh (Universitas Muhammadiyah Surabaya, 2025)
The purpose of the researcher in conducting the research was to determine the application of Project Based Learning (PjBL) to improve learning outcomes. The procedure used by the researcher in the research was classroom action research with four stages, namely: planning, implementation, observation, reflection. The research participants were 32 students of class X MPK 3 SMK Adhikawacana Surabaya. The research data came from the analysis of the average pretest and posttest of students. Through this research, it can be seen that the application of the Project Based Learning (PjBL) learning model can help improve learning outcomes, as evidenced by the average pretest and posttest of cycle 1 experiencing an increase in learning outcomes indicated by an average of 60.1 to 80.2. The results of the cycle 1 posttest showed that out of a total of 32 students, 26 of them had completed and 6 had not completed. Cycle 2 also experienced an increase in learning outcomes indicated by the average pretest and posttest values ​​of cycle 2 which increased from an average of 66.2 to 84.1. In the results of the posttest of cycle 2, it was found that of the total number of students, 27 of them had achieved completion and 5 had not achieved completion.